Micro sourcing framework to uplift income of the poor / Noor Habibah Arshad … [et al.] - Arshad, Noor Habibah; Salleh, Siti Salwa; Mastuki, Norazam; Janom, Norjansalika; Syed Aris, Syaripah Ruzaini (Research Innovation Business Unit, 2014)
The role of ICT among poor people and communities has increased tremendously. One of the ICT industries is the micro sourcing industry which has been identified as a potential industry to help increase income for the poor in Malaysia. Micro sourcing is an effective way to accomplish tedious task at a faster rate. It involves large projects that are broken down into micro tasks. These micro tasks are well-defined and then distributed to a group of workers. Micro sourcing workers have the flexibility of doing work at a time, location and pace of their choice. It also provides an additional income to complement existing income. Currently, the existing micro souring business models in Malaysia involve three groups namely Job Providers, Platforms and Micro workers. Job providers will outsource their jobs to micro sourcing platforms. The number of job providers is also quite limited and concentrated within the private sector. In the local market the number of platforms is relatively small and their roles are very limited; as mediator between job providers and micro workers. They advertise the task source from job providers and once tasks are completed by micro workers; they verify those tasks before submitting them to the job providers. Their role in the local micro sourcing industry is not as wide as international platforms. When a task is advertised on a platform, micro workers will pull the task based on their interests. After the task is completed, the micro workers submit the job together with proof of task completion to the platform. Once the task is verified as completed by the platform, the micro workers will get paid directly by the job provider. However, the tasks available in the market are not targeted at any specific micro workers and these workers are not given proper training to perform the task. The existing scenario could make the industry unsustainable in the long run. To run a micro sourcing industry, there are several framework and models proposed such as FORT framework, Structuration Theory and Entrepreneurial model. Based on the framework and models stated above, it is clear that the framework/models are limited to profitable business operations and not into providing equitable opportunity to participate in the economy as well as work towards greater socioeconomic status in terms of upgrading the quality of life of the poor. In light of these, we have developed strategic framework based on the five Strategic Thrusts identified. The Strategic Thrusts are harnessing demand side (job providers) of domestic and international market; platform capacity and capability building; leverage and utilise existing infrastructure; uplift and enhance capability of the supply side (micro workers); and instruments to expedite growth of local micro sourcing industry. The Strategic Framework is intended to provide strategic direction at national level to all stakeholders; to highlight key areas that need to be addressed in order to grow a sustainable micro sourcing industry in the country; and to serve as a guideline in the implementation of programs and plans related to micro sourcing industry development. This framework cuts across multiple sectors and thus, requires different types of government support from different ministries and agencies. Other stakeholders also have to perform their roles to ensure the effectiveness of the proposed strategic framework. With more support from these stakeholders, this industry would be able to achieve its true economy and would be able to help improve the socioeconomic status of the low income group in Malaysia.